Molecular imaging of a fluorescent antibody against epidermal growth factor receptor detects high-grade glioma - Quan Zhou (Nature Portfolio, 2021)
Abstract The prognosis for high-grade glioma (HGG) remains dismal and the extent of resection correlates with overall survival and progression free disease. Epidermal growth factor receptor (EGFR) is a biomarker heterogeneously expressed in HGG. We assessed the feasibility of detecting HGG using near-infrared fluorescent antibody targeting EGFR. Mice bearing orthotopic HGG xenografts with modest EGFR expression were imaged in vivo after systemic panitumumab-IRDye800 injection to assess its tumor-specific uptake macroscopically over 14 days, and microscopically ex vivo. EGFR immunohistochemical staining of 59 tumor specimens from 35 HGG patients was scored by pathologists and expression levels were compared to that of mouse xenografts. Intratumoral distribution of panitumumab-IRDye800 correlated with near-infrared fluorescence and EGFR expression. Fluorescence distinguished tumor cells with 90% specificity and 82.5% sensitivity. Target-to-background ratios peaked at 14 h post panitumumab-IRDye800 infusion, reaching 19.5 in vivo and 7.6 ex vivo, respectively. Equivalent or higher EGFR protein expression compared to the mouse xenografts was present in 77.1% HGG patients. Age, combined with IDH-wildtype cerebral tumor, was predictive of greater EGFR protein expression in human tumors. Tumor specific uptake of panitumumab-IRDye800 provided remarkable contrast and a flexible imaging window for fluorescence-guided identification of HGGs despite modest EGFR expression.